On Some new Results of a Subclass of Meromorphic Univalent Functions with Negative Coefficients Defined by liu – Srivastava Linear Operator - Mohammed Darweesh, Amal (International Journal of Engineering and Technology, 2018)
In this paper, we introduce and study a new subclass of meromorphic univalent functions with negative coefficients defined by Liu – Srivastava linear operator in the  We obtain some properties like, coefficients inequalities, growth and distortion theorems, closure theorems, partial sums and convolution properties.